2010
DOI: 10.1016/j.jconrel.2010.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue as a drug delivery system

Abstract: Fibrin glue has been used surgically for decades for hemostasis as well as a sealant. It has also been researched as both a gel for cell delivery and a vehicle for drug delivery. The drug delivery applications for fibrin glue span tissue engineering to chemotherapy and involve several mechanisms for drug matrix interactions and control of release kinetics. Additionally, drugs or factors can be loaded in the gel via impregnation and tethering to the gel through covalent linkages or affinity based systems. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 56 publications
2
115
0
1
Order By: Relevance
“…257 Platelets store essential GF, including PDGF, TGF-b, IGF-1, and EGF. 238,239,253,284 PRP may act as an exogenous source of TGF-b for bone healing, directing BMSCs to resorption sites. 285 Furthermore, platelets contain different angiogenic factors, such as VEGF, Ang-2, FGF-2, and antiangiogenic proteins, including endostatin and thrombospondin-1, regulating the formation of new blood vessels.…”
Section: (2011)mentioning
confidence: 99%
See 1 more Smart Citation
“…257 Platelets store essential GF, including PDGF, TGF-b, IGF-1, and EGF. 238,239,253,284 PRP may act as an exogenous source of TGF-b for bone healing, directing BMSCs to resorption sites. 285 Furthermore, platelets contain different angiogenic factors, such as VEGF, Ang-2, FGF-2, and antiangiogenic proteins, including endostatin and thrombospondin-1, regulating the formation of new blood vessels.…”
Section: (2011)mentioning
confidence: 99%
“…285 Furthermore, platelets contain different angiogenic factors, such as VEGF, Ang-2, FGF-2, and antiangiogenic proteins, including endostatin and thrombospondin-1, regulating the formation of new blood vessels. 232,239,284 Localized angiogenic factor delivery has proven beneficial for bone regeneration in various animal models by promoting neovascularization, bone turnover, osteoblast migration, and mineralization. Considering that PRP can release factors involved in angiogenesis, platelet concentrates have been used aiming for that goal.…”
Section: (2011)mentioning
confidence: 99%
“…The use of adhesives provides several advantages that include: rapid application, unnecessary administration of anesthetics, no trauma is induced to tissues, less pain, unnecessary sutures or staples removal and improved cosmetic results. Tissue adhesives may also be used as delivery systems and can be engineered for slow, localized release of bioactive molecules (Spicer & Mikos, 2010), such as pain treatment drugs or antibiotics (Fujimoto et al, 1997). They can be used as vehicles to growth factors (Catelas et al, 2008), and cell lines to assist on healing, namely, in poorly healing tissues like cartilage (Hoemann et al, 2005).…”
Section: Bioadhesivesmentioning
confidence: 99%
“…They can be used as vehicles to growth factors (Catelas et al, 2008), and cell lines to assist on healing, namely, in poorly healing tissues like cartilage (Hoemann et al, 2005). Very recently, Spicer & Mikos (2010) reported several studies concerning the entrapment of drugs and growth factor in fibrin gels. Entrapment of such bioactive compounds was achieved by simply mixing the components before crosslink of the fibrinogen.…”
Section: Bioadhesivesmentioning
confidence: 99%
“…Fibrin glue can also be used as a drug delivery device for growth factors (GFs), either in combination with cell transplantation or not. Several studies have shown that fibrin glue can provide sustained release of GFs during a few days to one week (Spicer & Mikos, 2010). Longer GF retention times can be achieved by modifications in the GF (Schmoekel et al, 2004), by integrating high GF-affinity moieties in the fibrin chains (Merritt et al, 2010), or by covalent linking of the GFs (Drinnan et al, 2010;Schmoekel et al, 2005).…”
Section: Fibrinmentioning
confidence: 99%